Association of cetylated fatty acid treatment with physical therapy improves athletic pubalgia symptoms in professional roller hockey players. Issue 7 (July 2020) - Pampaloni, Enrico; Pera, Elena; Maggi, Duilio; Lucchinelli, Riccardo; Chiappino, Dante; Costa, Andrea; Venturini, Veronica; Tarantino, Germano
Abstract: Background: Athletic pubalgia (AP), a frequent problem among professional roller hockey players (PRHPs), consists of lower abdominal and groin pain, without the presence of true hernia. Aims: We assessed cetylated fatty acids (CFAs) in association with conservative therapy for treatment of AP in PRHPs. Methods: Ultrasound examination was performed before and after treatment. Strength tests were performed and AP-related pain was measured during the treatment period. Findings: Nine of 10 enrolled PRHPs completed a 12-week treatment with CFAs in association with conservative therapy, consisting of manual therapy, diathermy or ultrasonography. Initial ultrasound examination showed AP signs in 7 (70%) of 10 PRHPs. After 12 weeks of therapy, these signs could only be detected by ultrasound in 2 (22.2%) of 9 PRHPs. An increase in muscle strength (already after first week of treatment) and a reduction of AP-related pain were also observed during the treatment. Conclusion: The association of CFA treatment with a conservative rehabilitation therapy improves muscle strength and pain and may accelerate recovery from AP. Abstract : Musculoskeletal system; Medical imaging; Clinical research; Health profession; Diagnostics; Athletic pubalgia; Cetlyated fatty acids; Physical therapy; Sports hernia; Strength test; Ultrasound.